BEBERAPA ASPEK BUDAYA DALAM SASTRA LISAN SUKU MOY - Sri Yono NFN (Balai Bahasa Provinsi Papua, 2019)
As a part of culture that grows and exists among its society, oral literature plays an important role among them. The existence of oral literature is becoming a medium to explore the culture of such society because the core of literature is culture. This literature anthropology research is aimed to know the oral literature of Moy tribe focused on cultural aspects such as technology, religion, myth, law, and art by applying descriptive qualitative approach. Based on the analaysis of the cultural aspects in oral literature Moy tribe, it is known that their myth could be used as a medium to have a comprehesif understanding of their culture.